Anthropometric and physical characteristics of elite team handball players according to axes and lines playing positions - Cherif, M.; Matos Da Costa, A. (Global journal for research analysis, 2013)
The purpose of this study was to compare (i) anthropometric data and physical performance characteristics between different axis and lines playing positions of professional team handball players and (ii) performance profiles between 1st division and national Tunisian team handball players. Forty four male professional handball players with a mean age of 22.09 ± 2.56 years and 12 years of playing experience at national level participated in this study. Measurement of anthropometric data, repeated sprint ability, jumping performance, and endurance performance were determined and analyzed with respect to axis and lines playing position. The result showed that players of national team were taller (p<0.05), had significantly (p<0.01) better performance in squat and countermovement jump and a higher (p<0.05) maximal oxygen uptake. Similarly, players of central axe reached highest size, weight and thin mass. Players of lateral axis had higher, maximal oxygen uptake, maximal speed and jumping performance. While, players of rear lines reached highest age. These results demonstrate that international players were characterized by hghest average of age, size, jumping performance and maximal oxygen uptake than those of 1st division team. Players of latéral axis reached the best performances in endurance and jumping performance than players of central axe. However, Play makers and pivots reached highest size, weight and thin mass